Bromate Removal from Water Using Ion Exchange Resin: Batch and Fixed Bed Column Performance - SAFAL MESTRI (Ozone: Science & Engineering, 2023)
In this study, the removal of bromate, a regulated ozone by-product, was evaluated using a strong-base anion (SBA) exchange resin in batch and column experiments. The kinetics studies in batch mode showed that film diffusion-controlled bromate exchange in SBA and the isotherm studies showed that the Langmuir model fitted the experimental results with a maximum exchange capacity of 296.66 mg BrO3−/g (~1.3 meq/mL resin). In the fixed-bed column studies, breakthrough curves were obtained under different operating conditions to examine the effects of feed flow rate, inlet bromate concentration, and bed height on column performance. A modified n-order Bohart and Adams model (n-BAM-c), which considered the asymmetry of the breakthrough curve and flow channeling, was applied for the first time to describe the experimental data obtained from the column and to predict the breakthrough curves. It was found that n-BAM-c fitted the experimental data well (R2 > 0.99) and the effects of the key operating conditions on the model parameters were determined. Overall, the results show that SBA exchange is suitable for bromate removal from water and n-BAM-c could be a powerful tool for the design and upscaling of bromate ion exchange columns.